Carrier signal based sensorless control of electrically excited synchronous machines at standstill and low speed using the rotor winding as a receiver - Rambetius, Alexander; Ebersberger, Sebastian; Seilmeier, Markus; Piepenbreier, Bernhard (Power Electronics and Applications (EPE), 2013 15th European Conference, 2013)
This paper presents a new carrier signal based approach for motion sensorless control of electrically excited synchronous machines. In the case of permanent magnet synchronous machines sensorless control at standstill and low speed is mostly done by injecting a high-frequency voltage and evaluating the resulting current response. Hence, the stator is used as the transmitter and as the receiver of the carrier signal. The major drawback is that a magnetic saliency is mandatory. In the case of electrically excited synchronous machines the rotor voltage serves as an additional input to the system and the resulting field current as an additional, easy to measure, state variable. The presented approach makes use of this fact and uses the field winding as the receiver of a carrier signal, which is injected into the stator winding. Like this no magnetic saliency is mandatory in order to track the position. The new approach is compared to a well-known carrier signal based method, in which the stator works as the transmitter and as the receiver of the carrier signal. In this case a magnetic saliency is mandatory which differs from the saliency necessary for permanent magnet synchronous machines. The applicability of both approaches is proven in experiments. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.carrie
Keywords: Sensorless control; Synchronous motor; Traction application; Vector control

Flatness Based Sensorless Control of PMSM Using Test Current Signal Injection and Compensation for Differential Cross-Coupling Inductances at Standstill and Low Speed Range - Piepenbreier, Bernhard; Seilmeier, Markus; et al. (IEEE International Symposium on Sensorless Control for Electrical Drives and Predictive Control of Electrical Drives & Power Electronics (SLED-PRECEDE 2013), 2013)
This paper presents a novel flatness based two-degree-of-freedom (2DoF) sensorless control scheme for PMSM at standstill and for low speed range using test current signal injection in the estimated d-axis of the field oriented dq-coordinate system. Asymmetrical winding and saturation might cause the occurrence of differential cross-coupling inductances and as a result the estimated rotor position deviates from the real value. The differential cross-coupling inductances have to be compensated for to overcome this problem. For that a flatness based dynamic feed-forward control is proposed. The control error due to model uncertainties is minimized using a controller that fulfills the internal model principle. The control signal of the high frequency controller in the q-axis is demodulated and afterwards used as the input signal of a tracking-observer to estimate the rotor position. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.flatne
Keywords: Inductances; Permanent magnet machines; Sensorless control; State-space methods

Flatness Based Sensorless Control of PMSM Using Test Current Signal Injection and Compensation for Differential Cross-Coupling Inductances at Standstill and Low Speed Range - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (2013)
This paper presents a novel flatness based two-degree-of-freedom (2DoF) sensorless control scheme for PMSM at standstill and for low speed range using test current signal injection in the estimated d-axis of the field oriented dq-coordinate system. Asymmetrical winding and saturation might cause the occurrence of differential cross-coupling inductances and as a result the estimated rotor position deviates from the real value. The differential cross-coupling inductances have to be compensated for to overcome this problem. For that a flatness based dynamic feed-forward control is proposed. The control error due to model uncertainties is minimized using a controller that fulfills the internal model principle. The control signal of the high frequency controller in the q-axis is demodulated and afterwards used as the input signal of a tracking-observer to estimate the rotor position.
Keywords: Sensorless control; Permanent magnet machines; State-space methods; Inductances

HF Test Current Injection Based Self-Sensing Control of PMSM for Low and Zero Speed Range Using Two-Degree-of-Freedom Current Control. - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives (SLED 2014), 2014)
This paper deals with an innovative self-sensing control scheme based on test current instead of voltage injection. Using Two-Degree-of-Freedom current control one can overcome the bandwidth limitations which made test current injection unattractive during the last 20 years. The Two-Degree-of-Freedom control scheme consists of a model based dynamic feed forward control to set the reference response and model reference tracking controllers providing disturbance rejection and the position error signals for self-sensing control. Since Two-Degree-of-Freedom control is a model based control scheme the compensation for secondary saliencies is inherently included in the pre-control. It is shown analytically that in case of test current instead of voltage injection just the precise knowledge of the current and position dependent inductance mqd HF is needed in case of inductance saliency based sensorless control. The effectiveness of the proposed method is proven by experimental results. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.hftest
Keywords: permanent magnet motors; saliency; sensorless control; test current injection

HF Test Current Injection Based Self-Sensing Control of PMSM for Low and Zero Speed Range using Two-Degree-of-Freedom Current Control - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (2014)
This paper deals with an innovative self-sensing control scheme based on test current instead of voltage injection. Using Two-Degree-of-Freedom current control one can overcome the bandwidth limitations which made test current injection unattractive during the last 20 years. The Two-Degree-of-Freedom control scheme consists of a model based dynamic feed forward control to set the reference response and model reference tracking controllers providing disturbance rejection and the position error signals for self-sensing control. Since Two-Degree-of-Freedom control is a model based control scheme the compensation for secondary saliencies is inherently included in the pre-control. It is shown analytically that in case of test current instead of voltage injection just the precise knowledge of the current and position dependent inductance m(qd)(HF) is needed in case of inductance saliency based sensorless control. The effectiveness of the proposed method is proven by experimental results.
Keywords: permanent magnet motors; sensorless control; saliency; test current injection

HF Test Current Injection-Based Self-Sensing Control of PMSM for Low- and Zero-Speed Range Using Two-Degree-of-Freedom Current Control - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (IEEE Transactions on Industry Applications, 2015)
This paper deals with an innovative self-sensing control scheme based on test current instead of voltage injection. Using two-degree-of-freedom current control, one can overcome the bandwidth limitations that made test current injection unattractive during the last 20 years. The two-degree-of-freedom control scheme consists of a model-based dynamic feedforward control to set the reference response and model reference tracking controllers providing disturbance rejection and position error signals for self-sensing control. Since two-degree-of-freedom control is a model-based control scheme, the compensation for secondary saliencies is inherently included in the precontrol. It is analytically shown that, in the case of alternating test current instead of voltage injection, just the precise knowledge, in general, of the current- and position-dependent secondary diagonal element of the inductance matrix is needed in the case of inductance saliency-based self-sensing control. The effectiveness of the proposed method is proven by experimental results.
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.LEEAS.hftest
Keywords: Current control; eddy currents; machine vector control; magnetic losses; motion control; permanent-magnet machines; permanent-magnet motors; saliency; self-sensing control; sensorless control; test current injection

HF Test Current Injection-Based Self-Sensing Control of PMSM for Low- and Zero-Speed Range Using Two-Degree-of-Freedom Current Control - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (IEEE Transactions on Industry Applications, 2015)
This paper deals with an innovative self-sensing control scheme based on test current instead of voltage injection. Using two-degree-of-freedom current control, one can overcome the bandwidth limitations that made test current injection unattractive during the last 20 years. The two-degree-of-freedom control scheme consists of a model-based dynamic feedforward control to set the reference response and model reference tracking controllers providing disturbance rejection and position error signals for self-sensing control. Since two-degree-of-freedom control is a model-based control scheme, the compensation for secondary saliencies is inherently included in the precontrol. It is analytically shown that, in the case of alternating test current instead of voltage injection, just the precise knowledge, in general, of the current- and position-dependent secondary diagonal element of the inductance matrix is needed in the case of inductance saliency-based self-sensing control. The effectiveness of the proposed method is proven by experimental results.
Keywords: Current control; eddy currents; machine vector control; magnetic losses; motion control; permanent-magnet machines; permanent-magnet motors; saliency; self-sensing control; sensorless control; test current injection

High Precision Identification Method for differential dq-Inductances of Permanent Magnet Synchronous Machines - Reill, Josef; Kellner, Sven; Ebersberger, Sebastian; Seilmeier, Markus; Piepenbreier, Bernhard (International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.highpr

High Precision Identification Method for differential dq-lnductances of Permanent Magnet Synchronous Machines - Seilmeier, Markus; Ebersberger, Sebastian; Kellner, Sven; Piepenbreier, Bernhard; Reill, Josef (2010)
This paper presents a novel method to measure the dq-inductances of permanent magnet synchronous motors (PSM). Accurate knowledge of the machine parameters is very important for high precision field oriented control of PSMs. Additionally there is a trend towards sensorless control of this type of machine. Especially sensorless control with test signals is based on the differential inductances. However, the parameters vary during operation. On the one hand the inductances and the permanent magnet flux mainly depend on the load of the machine. On the other hand the stator resistance changes with temperature. As there actually exist methods to get the absolute dq-inductances this topic is kept short. The focus in this publication is set to the differential inductances.The authors propose a high frequency signal based method to analyse the load and frequency dependent differential inductances in the rotor reference frame with very high precision. The method was tested in the laboratory with different machines and brought reliable results.

Identification of Differential Inductances of Permanent Magnet Synchronous Machines Using Test Current Signal Injection - Piepenbreier, Bernhard; et al. (SPEEDAM 2012, 2012)
In this paper a new kind of identification method for differential self and mutual inductances of permanent magnet synchronous machines (PMSMs) is proposed. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.identi_1
Keywords: cross-saturation; differential inductances; high frequency current injection method; permanent magnet synchronous machines; proportional-resonant current control

Identification of high frequency resistances and inductances for sensorless control of PMSM - Ebersberger, Sebastian; Seilmeier, Markus; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives and Predictive Control of Electrical Drives & Power Electronics (SLED-PRECEDE 2013), 2013)
Recently published papers show that also a saliency in the high frequency (HF) resistances can be used for sensorless control. Those papers assume a diagonal HF resistance matrix. The aim of this paper is to show, based on experimental results, that a phenomenon like cross-saturation for the inductances is also existent for the HF resistances. The voltage drops caused by the HF resistances are typically very small and thus their identification is challenging. Therefore a high precision 3-phase current measurement is used and the dead-time and voltage drop errors caused by the inverter are compensated for. A high frequency test current control allowing zero steady-state control error is needed to overcome the limitations of voltage injection based methods. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.identi

Identification of high frequency resistances and inductances for sensorless control of PMSM - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (2013)
Recently published papers show that also a saliency in the high frequency (HF) resistances can be used for sensorless control. Those papers assume a diagonal HF resistance matrix. The aim of this paper is to show, based on experimental results, that a phenomenon like cross-saturation for the inductances is also existent for the HF resistances. The voltage drops caused by the HF resistances are typically very small and thus their identification is challenging. Therefore a high precision 3-phase current measurement is used and the dead-time and voltage drop errors caused by the inverter are compensated for. A high frequency test current control allowing zero steady-state control error is needed to overcome the limitations of voltage injection based methods.

Impact of Three-Phase Current Measurement on Field-Oriented Control - Piepenbreier, Bernhard; et al. (Power Conversion Intelligent Motion (PCIM), 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.impact

Lagegeberlose Positionsregelung eines permanenterregten Synchronlinearmotors - Ebersberger, Sebastian; Piepenbreier, Bernhard (at - Automatisierungstechnik, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.lagege_5

PMSM d,q-Reference Frame Model using Absolute and Differential Inductance Surfaces - Ebersberger, Sebastian; Kellner, Sven; Piepenbreier, Bernhard (Power Conversion Intelligent Motion (PCIM), 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.pmsmdq

PMSM Model for Sensorless Control Considering Saturation Induced Secondary Saliencies - Ebersberger, Sebastian; Seilmeier, Markus; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives and Predictive Control of Electrical Drives & Power Electronics (SLED-PRECEDE 2013), 2013)
Saliencies in electric machines are caused by the machine geometry and saturation. PMSM typically do not just show a single sinusoidal saliency, which is the main saliency utilized for position tracking. Secondary saliencies are a major source of deterioration for sensorless control, whereby saturation is reported to be the main problem. Cross-saturation, caused by a movement of the main flux away from the d-axis, results in steady-state position estimation errors. Moreover saturation can result in 6n-harmonic components in the inductances in field oriented coordinates. This effect causes position dependent estimation errors. Both effects need to be compensated for, if significant. For model based compensation a machine model with time-variant parameters is needed to cope with nonlinear material characteristics. A general machine model in field oriented coordinates considering multiple saliencies is derived and a method for systematic determination of the position dependent inductances is proposed. The machine model is verified by test bench measurement results. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.pmsmmo

PMSM Model for Sensorless Control Considering Saturation Induced Secondary Saliencies - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (2013)
Saliencies in electric machines are caused by the machine geometry and saturation. PMSM typically do not just show a single sinusoidal saliency, which is the main saliency utilized for position tracking. Secondary saliencies are a major source of deterioration for sensorless control, whereby saturation is reported to be the main problem. Cross-saturation, caused by a movement of the main flux away from the d-axis, results in steady-state position estimation errors. Moreover saturation can result in 6n-harmonic components in the inductances in field oriented coordinates. This effect causes position dependent estimation errors. Both effects need to be compensated for, if significant. For model based compensation a machine model with time-variant parameters is needed to cope with nonlinear material characteristics. A general machine model in field oriented coordinates considering multiple saliencies is derived and a method for systematic determination of the position dependent inductances is proposed. The machine model is verified by test bench measurement results.

Sensorless Control of PMSM for the Whole Speed Range using Two-Degree-of-Freedom Current Control and HF Test Current Injection for Low-Speed Range - Piepenbreier, Bernhard; Ebersberger, Sebastian; Seilmeier, Markus (IEEE Transactions on Power Electronics, 2015)
In this paper, an innovative sensorless two-degree-of-freedom current control scheme for the whole speed range is proposed. It consists of a model-based dynamic feedforward control to set the reference response and model reference tracking controllers providing disturbance rejection and the position error signals needed for sensorless control. For low- and zero-speed operation, alternating test current injection is used to gain a position error signal. A flatness-based test signal precontrol provides compensation for secondary saliencies like cross-saturation and higher harmonics. For mid- and high-speed operation, it is shown how the model-based dynamic feedforward control can be modified to obtain a high-quality position error signal from the tracking controller. No additional model-based estimator evaluating back-EMF information is needed. The effectiveness of the proposed method is proven by experimental results.
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.LEEAS.sensor_4
Keywords: Permanent magnet motors; saliency; sensorless control; test current injection

Sensorless Control of Short Stator Permanent Magnet Synchronous Linear Machines - A Renewed Approach International Conference and Exhibition for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management - Ebersberger, Sebastian; Piepenbreier, Bernhard (PCIM Europe, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.sensor_1